A Learning Media Based on Hands-on Activity in Mathematics for Students Special School - Nurjanah, Nurjanah; Rohayati, Ade; Riza, Lala Septem (The Center for Disability Studies and Services Brawijaya University, 2021)
The use of hands-on activity-based mathematics learning media for mentally retarded children and cerebral palsy is largely unexplored. Meanwhile, observations of children with special needs (mental retardation and cerebral palsy) at school have not shown good basic math skills, such as counting, recognizing numbers, recognizing letters, performing math operations (for example, addition and subtraction). This study aims to develop a hands-on activity-based learning media model for mentally retarded children and cerebral palsy to improve understanding of mathematics in reading, writing, and arithmetic subjects. The method used is Research and Development, where the subject is the Special School in Bandung, Indonesia. The instruments used in this study were documentation, classroom observation, interviews, and tests of mathematical comprehension abilities. The results showed that a hands-on activity-based learning model could be used to improve basic math skills in reading, writing, and arithmetic for children with mental retardation and cerebral palsy.